2018
DOI: 10.1002/ece3.4263
|View full text |Cite
|
Sign up to set email alerts
|

Fire rather than nitrogen addition affects understory plant communities in the short term in a coniferous‐broadleaf mixed forest

Abstract: Increasing fire risk and atmospheric nitrogen (N) deposition have the potential to alter plant community structure and composition, with consequent impacts on biodiversity and ecosystem functioning. This study was conducted to examine short‐term responses of understory plant community to burning and N addition in a coniferous‐broadleaved mixed forest of the subtropical‐temperate transition zone in Central China. The experiment used a pair‐nested design, with four treatments (control, burning, N addition, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The csv files and R file have been deposited in Figshare, https://figshare.com/s/d2933788bc55814b47f3 ( 64 ). Previously published data were used for this work ( 8 , 27 , 34 , 43 , 44 , 53 , 65 …”
Section: Data Availabilitymentioning
confidence: 99%
“…The csv files and R file have been deposited in Figshare, https://figshare.com/s/d2933788bc55814b47f3 ( 64 ). Previously published data were used for this work ( 8 , 27 , 34 , 43 , 44 , 53 , 65 …”
Section: Data Availabilitymentioning
confidence: 99%
“…Immediately after fire, adequate growth space and resource availability greatly favor the establishment of vascular plants, which are fast-growing, nutrient-demanding, and shade-intolerant [8]. Moreover, higher soil temperatures are beneficial for breaking seed dormancy and promoting seed germination [36], while enhancing the abundance and diversity of understorey vegetation [37]. The cover and richness of understorey vegetation tend to peak within the first 40 years following fire disturbances in boreal forests [8].…”
Section: Colonization Timementioning
confidence: 99%
“…The relatively stable post‐Miocene history and establishment of semi‐arid and highly seasonal (Mediterranean‐type) climates in southwestern Africa have also been assumed to be major contributors to diversity (Goldblatt & Manning, ). Although a role for the presence of wildfire as a stimulus for species diversification was proposed long ago (Mutch, ), it has only received attention more recently (He, Lamont & Manning, ; Rundel et al, , ) and has been shown to have a dominant, even pre‐emptive, role compared with other likely environmental constraints (Hu et al, ; Lamont, He & Yan, ). In attempts to understand the distribution and diversity of species, disturbance by fire as a key agent of selection has long been overlooked, and continues to be so (Pausas & Lamont, ; Magadzire et al, ; Pausas & Bond, ).…”
Section: Introductionmentioning
confidence: 99%
“…In attempts to understand the distribution and diversity of species, disturbance by fire as a key agent of selection has long been overlooked, and continues to be so (Pausas & Lamont, ; Magadzire et al, ; Pausas & Bond, ). However, there is increasing evidence to suggest that prevailing fire regimes make a major contribution to explaining plant diversity at both the community (Burkle, Myers & Belote, ; Hu et al, ) and global (Pausas & Ribeiro, ) scales compared with other possible constraints.…”
Section: Introductionmentioning
confidence: 99%